A subterranean estuarine typology analogous to open-water estuaries - Bokuniewicz, Henry (Frontiers in Earth Science, 2023)
Subterranean estuaries (STEs), like open-water estuaries, are zones of mixing between seawater and freshwater. Despite the diverse manifestations of STEs, the mixing processes have elements in common with open-water estuaries, which can serve as a basis for their classification. A typology for STEs might provide a road map for further distilling a working definition of STEs. By analogy with open-water estuaries, a typology for STEs might include characteristic physical drivers and processes, morphology, and biologically relevant parameters. I suggest that such a typology be based on salinity structure to include at a minimum the (1) coastal slope, (2) tidal range, (3) hydraulic conductivity, and (4) recharge. Even a partially applicable definition permits classification, encourages comparisons and can provide a framework for management.